The pentose phosphate pathway mediates hyperoxia-induced lung vascular dysgenesis and alveolar simplification in neonates - Jiannan Gong; Zihang Feng; Abigail L. Peterson; Jennifer F. Carr; Xuexin Lu; Haifeng Zhao; Xiangming Ji; You-Yang Zhao; Monique E. De Paepe; Phyllis A. Dennery; Hongwei Yao (JCI Insight, 2021)
Dysmorphic pulmonary vascular growth and abnormal endothelial cell (EC) proliferation are paradoxically observed in premature infants with bronchopulmonary dysplasia (BPD), despite vascular pruning. The pentose phosphate pathway (PPP), a metabolic pathway parallel to glycolysis, generates NADPH as a reducing equivalent and ribose 5-phosphate for nucleotide synthesis. It is unknown whether hyperoxia, a known mediator of BPD in rodent models, alters glycolysis and the PPP in lung ECs. We hypothesized that hyperoxia increases glycolysis and the PPP, resulting in abnormal EC proliferation and dysmorphic angiogenesis in neonatal mice. To test this hypothesis, lung ECs and newborn mice were exposed to hyperoxia and allowed to recover in air. Hyperoxia increased glycolysis and the PPP. Increased PPP, but not glycolysis, caused hyperoxia-induced abnormal EC proliferation. Blocking the PPP reduced hyperoxia-induced glucose–derived deoxynucleotide synthesis in cultured ECs. In neonatal mice, hyperoxia-induced abnormal EC proliferation, dysmorphic angiogenesis, and alveolar simplification were augmented by nanoparticle-mediated endothelial overexpression of phosphogluconate dehydrogenase, the second enzyme in the PPP. These effects were attenuated by inhibitors of the PPP. Neonatal hyperoxia augments the PPP, causing abnormal lung EC proliferation, dysmorphic vascular development, and alveolar simplification. These observations provide mechanisms and potential metabolic targets to prevent BPD-associated vascular dysgenesis.